The genus Hybos Meigen (Diptera: Empidoidea: Hybotidae) in Thailand - Plant, Adrian R. (Zootaxa, 2013)
The genus Hybos Meigen in Thailand is revised and full descriptions and keys provided for all 41 species. Thirty-four new species are recognized: H. aceriformis sp. nov., H. ancyclochiles sp. nov., H. anisoserratus sp. nov., H. bispinatus sp. nov., H. chaweewani sp. nov., H. daugeroni sp. nov., H. divisus sp. nov., H. grootaerti sp. nov., H. hylobates sp. nov., H. inthanonensis sp. nov., H. kaluang sp. nov., H. khamfui sp. nov., H. konkaogwang sp. nov., H. lannaensis sp. nov., H. mangraii sp. nov., H. meeamnat sp. nov., H. men sp. nov., H. merzi sp. nov., H. ngachang sp. nov., H. paknok sp. nov., H. phahompokensis sp. nov., H. pisadaanus sp. nov., H. saenmueangmai sp. nov., H. shamshevi sp. nov., H. sinclairi sp. nov., H. songbai sp. nov., H. steatopygus sp. nov., H. stigmaticus sp. nov., H. subapicalis sp. nov., H. tetricus sp. nov., H. thaosaeo sp. nov., H. thepkaisoni sp. nov., H. tilokarati sp. nov., H. yungyak sp. nov. Seven species known previously from China are recognized: H. ancistroides Yang & Yang, H. apicihamatus Yang & Yang, H. longus Yang & Yang, H. particularis Yang, Yang & Hu, H. serratus Yang & Yang, H. xishuangbannaensis Yang & Yang, and H. zhejiangensis Yang & Yang. Eight informal species-groups are tentatively proposed based on characters of male and female terminalia and attention is drawn to the many previously overlooked taxonomically useful characters of the female terminalia. Distribution maps of all species are presented and distributions categorised as ‘widespread’, ‘eastern’, ‘southern’, north-eastern’ or ‘northern and western’. Species richness and endemicity are greatest in mid to high elevation evergreen forest biotopes of the northern mountains and areas of endemism are identified on the Luang Prabang, Daen Lao, Thanon Thongchai ranges and on the Isaan Plateau at least. Adult phenology is correlated with the rainy season in many species and preliminary analyses reveal that many high-elevation species have short emergence periods and restricted distributions, whereas some lowland species have longer emergence periods and wider distributions.